PERJANJIAN PEMBERIAN KUASA PENJUALAN BARANG BERGERAK DENGAN SISTEM TITIP PADA PERTOKOAN DAN PEMBAGIAN HAK SERTA KEWAJIBAN KONTRAKTAN DI SAMARINDA - Harry cahyadi (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACT Whereas the agreement for the granting of power of the sale of goods to the Titip system shall initially be made by an agreement between the parties. The Suppleir Party first submits an application with a custodial clause to the Trasdisional Shop / mall in the Mall area, which is then followed by an offer on all terms of the agreement referred to by the shopkeeper. After suppleir agreed to all the requirements specified by the suppleir has agreed to the terms of the aforementioned treaty, then the agreement can be realized that is by the delivery of goods by suppleir at the shop owner. The series of legal acts that can be legally qualified as an act of authorization from suppleir. In the deed of the agreement, as exemplified in sub-chapter I of chapter III, 12 chapters are determined which specify all matters relating to the agreement giving the power of sale of goods concerned, whether about salesman Titip, sales system. responsibility of the parties, sanctions in case of disputes due to non-fulfillment of performance, payment procedures, termination of agreement. Since the entire terms of the agreement for the granting of power of the sale of goods to the Titip system has been determined in full in the treaty deeds made under mutual agreement between the parties, the matters which allow for the dispute can be resolved.The parties have rights and obligations in accordance with the clauses that have been determined. The party receiving the rights / obligations shall have the rights and obligations, among others: The shopkeeper in each month shall be entitled to obtain a report from SPG / Salesperson on the sales turnover of goods within one month, if the SPG is supplied by suppliers; The shopkeeper is entitled to a commission of 25% of the proceeds from the sale of goods within a month; The shopkeeper is entitled to a report on changes in the stock of consignment / goods sold by the store; The shopkeeper has an obligation to report the proceeds of the sale of goods to the suppliers, if the SPG is provided by the dealer's shop; Provide payment of goods sold in every month on suppleir; Provides compensation for damages caused by fire.The authorizing party / supplier has the right and obligation, among others: Entitled to the payment of the sale of goods every month that is the 15th of the following month at Bank BCA Samarinda Branch; Entitled to get a report from the sale of goods on the calculation of turnover amount in each month based on the stock report; Obtain report on Titip location change; Obtaining compensation suffered by fire; The suppleir party is entitled to design Titip / shelf, and determine the price of the goods to be sold in the mall; Provide salesman Titip, give commissions, deliver goods, pay sales tax / VAT, report changes in stock of goods on the shop owner, which is the obligation of suppleir.